2022
DOI: 10.9734/jsrr/2022/v28i530520
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Therapeutic Benefits of Vitamin E after Paraquat Toxicity

Abstract: The Paraquat (1, 1-dimethyl-4,4-bipyridlium dichloride) is a non-selective nitrogen herbicide that is used for broadleaf control of weed. It has been shown that paraquat is toxic to human and animal. Vitamin E (α-tocopherol) is a lipid soluble antioxidant found in all cellular membranes. It helps in protecting the cell against lipid peroxidation. It has been documented that vitamin E has a protective effect against PQ-induced hematological toxicity in albino rats. This study was carried out to evaluate the hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Consistent with our findings, Yu et al noted that the elevation in serum potassium after acute PQ exposure could be attributed to renal failure and impaired potassium excretion 26 . Moreover, Okolonkwo et al showed that the substantial decline in blood hemoglobin levels might be associated with red blood cell destruction 27 . Upon administering PTX, a marked improvement was observed in hematocrit levels, likely due to enhanced membrane stability of red blood cells against oxidative damage induced by PQ.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Yu et al noted that the elevation in serum potassium after acute PQ exposure could be attributed to renal failure and impaired potassium excretion 26 . Moreover, Okolonkwo et al showed that the substantial decline in blood hemoglobin levels might be associated with red blood cell destruction 27 . Upon administering PTX, a marked improvement was observed in hematocrit levels, likely due to enhanced membrane stability of red blood cells against oxidative damage induced by PQ.…”
Section: Discussionmentioning
confidence: 99%